2007
DOI: 10.1002/jms.1196
|View full text |Cite
|
Sign up to set email alerts
|

Anomeric information obtained from a series of synthetic trisaccharides using energy resolved mass spectra

Abstract: The majority of structural investigations of oligosaccharides based on mass spectrometry use naturally occurring oligosaccharides, which do not allow extracting any common feature associated with anomeric structures and linkage positions. In order to address the issue to find such characteristics possibly contained in oligosaccharide structure, a synthetic combinatorial trisaccharide library was analyzed. The trisaccharides used in the analysis consisted of L-fucose, D-galactose and D-glucose, in which individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…It is interesting that B 1 ion was observed only for the ␤-Fuc compound ( ␤ 3␤␣), even though the ␣ difference between these two (3␣␣ and 3␤␣) is the ␣ anomeric configurations of the Fuc unit only. This result is puzzling because both of the product ions, B 1 and Y 1 ions, share a similar structure; however, this may suggest that ␤Fuc-Gal had more affinity with Na ␤ ␤ ϩ compared with its counter ␣-structure because a similar ␣ tendency was observed in a previous study [27]. In the CID spectrum of 3␤␤, 2,5 X 1 ion and an unusual fragment ion with m/z 187 were observed as characteristic ions.…”
Section: Cid Analysis Of All Compoundsmentioning
confidence: 79%
See 2 more Smart Citations
“…It is interesting that B 1 ion was observed only for the ␤-Fuc compound ( ␤ 3␤␣), even though the ␣ difference between these two (3␣␣ and 3␤␣) is the ␣ anomeric configurations of the Fuc unit only. This result is puzzling because both of the product ions, B 1 and Y 1 ions, share a similar structure; however, this may suggest that ␤Fuc-Gal had more affinity with Na ␤ ␤ ϩ compared with its counter ␣-structure because a similar ␣ tendency was observed in a previous study [27]. In the CID spectrum of 3␤␤, 2,5 X 1 ion and an unusual fragment ion with m/z 187 were observed as characteristic ions.…”
Section: Cid Analysis Of All Compoundsmentioning
confidence: 79%
“…We have analyzed isomeric oligosaccharides based on ERMS and shown that (1) the primary glycosidic linkage is more stable than the secondary glycoside linkage; and (2) ␣-glyco-␣ sides are more labile than ␤-glycosides, through inves-␤ tigation of malto (␣1¡4)-, ¡ ¡ isomalto (␣1¡6)-, and cello (␤1¡4)-oligosaccharid ¡ ¡ e [26] and trisaccharide libraries with the ␣/␤-Fuc-(1 ␤ ¡6)-␣/␤-Gal-(1 ␤ ¡6)-␣/␤-Glc-octyl ␤ sequence [27]. It is important to confirm the generality of these tendencies and at the same time to accumulate such data regarding the structure-related characteristics for future development of methods to identify novel glycoconjugates.…”
Section: Erms Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We also acknowledge that other research groups have successfully distinguished anomers by mass spectrometry [13][14][15][16][17][18][19][20]. Among them, we are particularly interested in the report by Leavell et al [1] because they studied conformations of metal complexes of sugars.…”
Section: Discussionmentioning
confidence: 98%
“…The dissociation of Fuc residues from a pair of precursor ions in the above case can be identified by ERMS (Figure 6). Since the method is very sensitive to the structural differences, it has been used to distinguish structurally closely related glycans [71][72][73][74][75].…”
Section: New Parameter For Use In Structural Analysismentioning
confidence: 99%